Efficacy, safety, and immunogenicity of an Escherichia coli-produced Human Papillomavirus (16 and 18) L1 virus-like-particle vaccine: end-of-study analysis of a phase 3, double-blind, randomised, controlled trial. Issue 12 (December 2022) - Zhao, Fang-Hui; Wu, Ting; Hu, Yue-Mei; Wei, Li-Hui; Li, Ming-Qiang; Huang, Wei-Jin; Chen, Wen; Huang, Shou-Jie; Pan, Qin-Jing; Zhang, Xun; Hong, Ying; Zhao, Chao; et al.
Summary: Background: This Escherichia coli -produced bivalent HPV 16 and 18 vaccine was well tolerated and effective against HPV 16 and 18 associated high-grade genital lesions and persistent infection in interim analysis of this phase 3 trial. We now report data on long-term efficacy and safety after 66 months of follow-up. Methods: This phase 3, double-blind, randomised, controlled trial was done in five study sites in China. Eligible participants were women aged 18–45 years, with intact cervix and 1–4 lifetime sexual partners. Women who were pregnant or breastfeeding, had chronic disease or immunodeficiency, or had HPV vaccination history were excluded. Women were stratified by age (18–26 and 27–45 years) and randomly (1:1) allocated by software (block randomisation with 12 codes to a block) to receive three doses of the E coli -produced HPV 16 and 18 vaccine or hepatitis E vaccine (control) and followed-up for 66 months. The primary outcomes were high-grade genital lesions and persistent infection (longer than 6 months) associated with HPV 16 or 18 in the per-protocol susceptible population. This trial was registered with ClinicalTrials.gov, NCT01735006 . Findings: Between Nov 22, 2012, and April 1, 2013, 8827 women were assessed for eligibility. 1455 women were excluded, and 7372 women were enrolled and randomly assigned to receive the HPV vaccine (n=3689) or control (n=3683). Vaccine efficacy was 100·0% (95% CI 67·2–100·0) against high-grade genital lesions (0 [0%] of 3310 participants in the vaccine group and 13 [0·4%] of 3302 participants in the control group) and 97·3% (89·9–99·7) against persistent infection (2 [0·1%] of 3262 participants in the vaccine group and 73 [2·2%] of 3271 participants in the control group) in the per-protocol population. Serious adverse events occurred at a similar rate between vaccine (267 [7·2%] of 3691 participants) and control groups (290 [7·9%] of 3681); none were considered related to vaccination. Interpretation: The E coli -produced HPV 16 and 18 vaccine was well tolerated and highly efficacious against HPV 16 and 18 associated high-grade genital lesions and persistent infection and would supplement the global HPV vaccine availability and accessibility for cervical cancer prevention. Funding: National Natural Science Foundation of China, National Key R&D Program of China, Fujian Provincial Project, Fundamental Funds for the Central Universities, Chinese Academy of Medical Sciences Innovation Fund for Medical Sciences, and Xiamen Innovax.